Preparation of Cell Wall Antigens of Staphylococcus aureus - Kowalski, J. J. (1970)
Cell walls were prepared from Staphylococcus aureus strains Copenhagen and 263 by high-speed mixing in the presence of glass beads followed by differential centrifugation. Insoluble peptidoglycan complexes were derived from cell walls by extraction of teichoic acid with 10% trichloroacetic acid. Intact teichoic acid was prepared from each strain by digestion of cell walls with lysostaphin and isolated by column chromatography. Soluble glycopeptide (peptidoglycan in which only the glycan has been fragmented) and the stable complex of teichoic acid with glycopeptide were prepared by digestion of cell walls with Chalaropsis B endo-N-acetylmuramidase and were separated by column chromatography. Amino acid and amino sugar contents of walls and subunits of walls were comparable to those reported by others.